CONTEXTS OF NEOLIBERAL GOVERNMENTS: DES(PATHS) OF PUBLIC POLICIES FOR THE INSERTION OF DIGITAL TECHNOLOGIES IN BASIC EDUCATION - Rodrigues, Gisele Soncini; Lima Menegasso, Mauriza Goncalves de; Furlan Costa, Maria Luisa [UNESP] (Fundacao Univ Tocantins, 2022)
The present work is result of a bibliographical research that aims to show the trajectory of neoliberal policies from its cradle in classical liberalism to its influence on public policies around education technology. The current moment raised the issue that brings up the debate on the importance of technologies in Basic Education. Was noticed that the history of educational technologies is marked by gain grounds and etbacks, a characteristic fact of the discontinuity policy of neoliberal governments. Therefore, it is urgent to implement actions of innovation in technology in school environments, in order to offer access to all students. We also verified that further research is necessary for a better understanding of the problem, which is a reflection of Adam Smith's minimal state, one of the authors studied in this article.
Keywords: Educational Technology; Neoliberalism; Educational Policies; Basic Education